PERMASALAHAN PELAKSANAAN PEMBELAJARAN DARING DI SEKOLAH DASAR PADA MASA PANDEMI COVID-19 (TINJAUAN TERHADAP IMPLEMENTASI PEMBELAJARAN TEMATIK) - Saidah, Karimatus; Trianingsih, Rima; Putri, Kharisma Eka (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to 1) know the implementation of thematic learning through online, 2) describe teacher strategies to maximize student learning activities and 3) identify problems in implementing online based learning. The research method used is a qualitative approach. Data collection techniques using online interviews. While the data analysis technique is done by collecting data, data reduction, data revision and data analysis. The results showed that the teacher could not implement online thematic learning even though the material presentation and assignments followed the themes in the teacher and student books. The teacher's strategy in implementing learning is by presenting instructional videos, presenting material documents equipped with voice notes, using quiz applications and visiting students at home. Obstacles in implementing online learning can be found in several aspects, including internet access, difficulty understanding materials and assignments, the diverse abilities of parents in accompanying their children to learn, and environmental conditions that are not suitable for online learning activities.